The Experience of Using Electronic Registers in Implementing Demographic Policy Actions in Developed Countries - Puhachova М. V. (Statistics of Ukraine, 2025)
Advanced systems for governance of big objects are inconceivable without information support based on innovative technologies. The country-level governance, with policy setting for various spheres of the societal activities being its integral component, also urgently requires large arrays of high-quality and easily accessible information. The current phase of information technology development enables to supply the public governance with such tools, which are systems of electronic registers and databases containing the data necessary for decision-making. The elaboration of an official demographic policy has its specific features caused by not only the importance of demographic processes going on in a country, but also by the complexity of accounting for many aspects affecting the life and health of country residents. A demographic policy needs to regulate the tendencies in birth rate, mortality rate, migration, age restructuring of the population (e.g., increases in the shares of young or old people), gender structure or regional redistribution of the population. Hence, creating and using the systems of electronic information resources containing electronic registers and databases pertaining to spheres like health care, education, social security, etc., as well as demographic registers containing the most complete information about the population enables to support demographic policy setting by the government. The article’s objective is to study the experience of using electronic registers designed for demographic policy setting in selected Western European countries possessing well-developed systems of electronic information resources and comparatively high demographic indicators. This objective was achieved by investigating the experiences of Norway and France. We believe that Norway can be regarded as a country that has one of the most sophisticated systems of registers and where death rate and life expectancy estimates are among the most favorable in Europe. France, being another country with a branching system of registers, is a leader in the developed world by overall birth rate and life expectancy ratios that are essentially higher than the EU average. In view of the experience of the developed European counties with comparatively good demographic situation and well-established systems of electronic information registers on which the governments can rely upon in elaborating respective actions, Ukraine needs to continue implementing digitalization of the national governance system.